(untitled) (The Agriculturists, 2010)
A survey was conducted in different districts of Barisal division in Bangladesh during May-June, 2008 to assess the production, consumption and marketing of livestock and their products. A total of 114 farmers were interviewed, of which 26, 24, 21, 10, 10 and 9 % were in Patuakhali, Barisal, Barguna, Bhola, Jhalakati and Pirojpur districts, respectively under Barisal division of Bangladesh. The livestock keeping patterns of farm households were cattle, buffalo, goat, chicken or duck or any combination of these. Cattle and chicken population was high in all farm categories and due to marshy area duck was higher in number compared to other region. Cattle and buffaloes were also reared by share system. Average milk production per cow was found 2.25 liter per day. The small and large farmers sold the highest portion of the product and the medium farmers consumed most of their products. On an average, all farm households spent 29, 18 and 19 % income generated through livestock for their daily expenses, agricultural inputs and food, respectively. On an average, health and veterinary expenditure per household was 6.95 US (1US=70BDT). Black quarter (23 %) and Foot and mouth disease (35 %) in cattle, Diarrhoea (39 %) and PPR (29 %) in goat, ranikhet (40 %) and fowl pox (34 %) in poultry were the common disease.